Social history of Islamic India 1605-1748 - "Yasin, Mohammad" (New Delhi, 1974)
This book presents the social history of Islamic India. This book covers following topics: The community; economic life; Muslims and Hindu; Festivities and Ceremonies; Indianization of the Community; Man and Moral Breakdown; India Islam in the first Millennium etc.
Keywords: Islam